Follicular flushing during oocyte retrieval in assisted reproductive techniques - Wongtra-Ngan S. (2014)
Ultrasound guided transvaginal aspiration of oocytes has replaced other methods of oocyte retrieval for in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI). However, there is controversy over whether flushing yields a larger number of oocytes and a higher potential for pregnancy than aspiration only.